Are Malaysian government-linked companies (GLCs) creating value? - Lau, Yeng Wai; Tong, Chue Qun (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
Government-linked companies (GLCs) play an important role in the development of the Malaysian economy. However, overall public perception of GLCs in Malaysia has been tainted by the poor performance of key players, namely Malaysia Airline System (MAS) and Proton Holdings Berhad. Results of prior studies on the extent to which government intervention affects a company’s performance are mixed. This study empirically assesses the impact of government intervention on firm value in the context of the Malaysian economy. Results of statistical analysis conducted on 15 GLCs over six years—i.e. 2000 to 2005—reveal a significant positive relationship between the degree of government ownership and firm value. In other words, this study has found that contrary to the adverse public perception of GLCs in Malaysia, government intervention improves firm value. Results of this study provide preliminary evidence on the effectiveness of the ownership and control structure of Malaysian GLCs in creating firm value. Such findings pave the way for future research on the extent to which the ownership and control structure of Malaysian GLCs can serve as a model for developing and third-world countries to emulate.